En la Montaña Mágica : enseñar Derecho Internacional Público - Simpson, Gerry (2010)
"Simpson, Gerry, On the Magic Mountain: Teaching Public International Law, in European Journal of International Law, vol. 10 (1999), p. 70. Translated into Spanish by Brian Frenkel and Milton Fellay. The editors wish to thank the author and the original publishers for their generosity in allowing the translation and reproduction of the article." -- In this essay, the author identifies a malaise in the teaching of International Law stemming from the fear of being confined to the academic periphery. This fear grows from the feeling that lawyers who practice International Law are considered neither "real" lawyers by some of our colleagues in law schools, nor sufficiently knowledgeable about global realities according to some international relations scholars. The response to these fears entails a series of compromises between "legalism" and "realism." The consequences of these compromises include theoretical incoherence and the depoliticization of the subject matter. These theoretical shortcomings lead professors to a mode the author calls "romantic." The romantic mode is attractive but also superficial and ultimately threatens to further empty international law of its political content. The author suggests three possible solutions to these problems. The first is to adopt a more comprehensive theoretical approach to teaching international law. The second is to embrace a more explicit political method in which the teaching of international law becomes an imaginative act of dissent. Finally, the author suggests a way of teaching context that avoids what is described in this work as the romantic malaise.